Mallorquí, Elvis (2021). Els camins històrics - Serra-Salvi, Anna (Documents d’Anàlisi Geogràfica, 2022)
Mallorquí, Elvis (2021) Els camins històrics Girona: Diputació de Girona, 96 p. ISBN 978-84-15808-96-1